2022
DOI: 10.1002/anie.202201327
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Valent Zirconocene‐Mediated Synthesis of Porphyrin(2.1.2.1)s and Its Extension to Synthesis of a Porphyrin(2.1.2.1) Nanobarrel

Abstract: Rosenthal's-reagent-mediated intramolecular cyclometallation of α,α-dialkynyldipyrrin nickel(II) complex and subsequent acid treatment afforded a 1,3butadiene-embedded porphyrin(2.1.2.1), 6, which served as a reactive diene towards dienophiles such as dimethyl acetylenedicarboxylate (DMAD) and benzyne to give corresponding Diels-Alder adducts. Diels-Alder reaction of 6 and benzdiyne gave adducts 14, 15 a, and 15 b along with a trace amount of porphyrin(2.1.2.1) barrel 13. Stepwise routes using 14 or 15 a/15 b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…The bond distances for [2,3]­F 5 TP and [3,4]­F 5 TP indicated that they are nonaromatic properties (Figure ). , The optimized structures of [2,3]­F 5 TP ( syn - and anti -isomers) and [3,4]­F 5 TP , obtained by DFT calculations, also supported the observation of nonaromaticity (Figure S19, SI). , …”
Section: Resultssupporting
confidence: 61%
“…The bond distances for [2,3]­F 5 TP and [3,4]­F 5 TP indicated that they are nonaromatic properties (Figure ). , The optimized structures of [2,3]­F 5 TP ( syn - and anti -isomers) and [3,4]­F 5 TP , obtained by DFT calculations, also supported the observation of nonaromaticity (Figure S19, SI). , …”
Section: Resultssupporting
confidence: 61%
“…This progress not withstanding, nanorings and nanobelts containing functional groups that would allow for postsynthetic modification, including metal cation complexation, remain rare. One attractive approach to such systems involves the use of porphyrins, classic planar and aromatic macrocycles whose rich functional chemistry is well documented . Anderson and co-workers and Osuka, Song et al have reported, respectively, template directed syntheses of wheel-like porphyrin oligomers and the metal-mediated preparation of belt-like porphyrins, respectively. However, systems that combine PAHs and the free pyrrolic functionality characteristic of porphyrins in a single discrete molecular belt-like arrangement are essentially unknown. , Herein, we report two isomeric nanosized pyrene-containing carboporphyrin hybrids, NB1 and NB2 (Scheme ), and show that these belt-like systems can be converted to their corresponding zinc complexes.…”
mentioning
confidence: 99%
“… [7c] Later, his group applied the metal‐templated cyclization to construction of ABCD porphyrins using Mg(II), Zn(II), and Ni(II) from ABCD‐functionalized bilanes (Figure 1D). [5b,7c] This strategy has also been applied to other porphyrinoids such as diazaporphyrin, [8a,b] norcorrole, [8c,d] and porphyrin(2.1.2.1) [8f] derivatives. In all compounds, the affinity of metal(II) ion for square‐planar geometry plays a crucial role.…”
Section: Introductionmentioning
confidence: 99%